(untitled) (CAHIERS MAGELLANES-NS, 2024)
This systematic review aims at comparing the therapeutic effectiveness and patients’ satisfaction between the clear aligners and fixed appliances. For the purpose of this study, the database sources that were used were PubMed, Scopus, and Web of Science and the papers included were from January 2005 till June 2024. It is also feasible to attest that retainer wearers present higher periodontal status when evaluated in regard to fixed appliances; there will be less plaque build up, and the bacteria in salivas related to caries. Moreover, when compared to the conventional aligners, clear aligners satisfy the patients several ways because of the comfort and appearance of the appliance product. This characteristic makes fixed appliances more set and the retention facets round brackets and wires that could let food particles together with the formation of plaque thus white spot lesions. However, the fixed appliances have the better alignment stability and occlusal outcomes in the simple cases more than the complex cases. The review also proclaims the importance of patient centeredness and the goals of treatment. More researches are recommended to enhance the techniques of employing clear aligners in clinical practice, especially the parts that demonstrated inefficiency in treating severe cases and the component of higher expenses. Hence, the source under consideration can be viewed as the practical evidenced review for clinicians wherein they are building up the evidence about their choice of orthodontic treatments together with the approaches based on the patient-oriented model and the assessment of clinical outcomes. I employed 20 best studies with 4 review articles for this research paper.